The power of alignment : - Labovitz, George H. (John Wiley & Sons, 1997)
Presents a breakthrough concept in clear and applicable terms, with an abundance of perspectives and examples from the field. The authors detail how to use alignment to simultaneously link the elements core to your business in a much more focused way and revitalize your organization's strategy, operations, and results.